Effect of Swimming Free 50 Meters for Males on Calcium Levels and Some Enzymes of Thyroid and Parathyroid Gland - Shatha Hazim Gorgees (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This study aimed to investigate the effect of swimming free 50 meters on calcium levels and activities of some key enzymes involved in calcium metabolism in males.